Optimization of Culture Conditions for Production and Activity of Thermostable Amylase by using Bacillus Strain A4 - Mina Kumari, Ch.; Bhaskar Reddy, I. (Asian Journal of Chemistry, 2010)
The present study deals with the production and activity of thermostable amylase by using Bacillus strain A4. The conditions for production of amylase was optimized. Maximum production of amylase was obtained in presence of wheat bran (270 U/mL) and cassava flour (110 U/mL) after 48 h of incubation. The optimum temperature and pH were found to be 50 ºC and 10, respectively. Maximum activity was observed at pH 9.0 at 90 ºC in crude extract, after 20 min of incubation. The presence of EDTA and SDS inhibits enzyme activity whereas Mn2+ and Fe2+ ions increased the amylase activity. Due to maximum production of amylase in presence of cheap, low concentration of substrates, stability at alkaline pH and high temperature, all the above characteristics makes the Bacillus strain A4 and its enzyme useful in different industries.